Descriptive analysis of nematode management practices and Nematodirus battus control strategies on UK sheep farms. (10th August 2021) - Melville, Lynsey A.; Innocent, Giles; Van Dijk, Jan; Mitchell, Sian; Bartley, David J.
Abstract: Background: Farm management practices have a major impact on nematode population dynamics. The presented study aimed to understand current nematode management practices on UK sheep farms; with a particular focus on Nematodirus battus because of the changing epidemiology, and emerging anthelmintic resistance observed in this species. Methods: A 42 question online survey covering grazing management, farm demographics and parasite control strategies was developed and distributed to the farming community in 2016. Analysis of the 187 completed questionnaires explored regional variations in practices. Results: Uptake of recommendations was variable, particularly quarantine practices and monitoring tools. Results also highlighted variation in the epidemiology of N. battus; respondents in the north (Scotland, north‐west and north‐east England) typically reported N. battus in spring with a perception of more severe clinical symptoms than those from the south (Midlands, Wales, south‐east and south‐west England; p = 0.03). Farms in the south observed greater changes in the timing of disease ( p = 0.006) with N. battus being reported throughout the year on some holdings and more frequent use of faecal egg count monitoring ( p = 0.006). Conclusions: Control of N. battus infection is challenging and 'one‐size‐fits‐all' advice is not applicable; however, the information gathered will enable the development of effective, adaptable control strategies.